MEMBANGUN LOYALITAS KONSUMEN MELALUI RELATIONSHIP MARKETING - Nirma Kurriwati (Eco-Entrepreneur, 2017)
The aims of this research is to find the influence of Customer Relationship Marketing's variables that are consist Bonding, Emphaty, Reciprocity, and Trust that did influence simultaneously as well as partial on loyality customer and also to know which one from the fourth variables of Customer Relationship Marketing highest or dominant to loyality customer. The method which used on this research is quantitative methods, that is the research which based on positive ideology which have the aim to Test the hypothesis that had been set up. The sample of this research is the customer  which totally are 97 respondents. The methods which used to take the sample are insidental sampling and reability purposive sampling. To examine the instrument the writer used the test of validity and reability, whereas the technique which used analyze the data to test the hypotesis is double regression linear which used test F (simultan) and test T (parsial). The result of this research show that customer relationship marketing variables which are : Bonding, Emphaty ,Reciprocity, and Trust simultaneously which influence significantly to loyality customer, customer relationship marketing variables which are Bonding, Emphaty, Reciprocity, and trust that influence significantly to loyality customer and from the fourth customer ralationship marketing variables that trust is the variable which influence is highest/ dominant to loyality customer.